The Sources Basis of the Problem of Implementation of Advanced Teaching Experience (the 2nd Half of the 20th Century) - Iryna Zhorova (Pedagogical Discourse, 2013)
The article examines the problem of studying, generalization and implementation of the advanced teaching experience of the 2nd half of the 20th century. Particularly on the basis of normative and legislative documents (orders, regulations), transcripts, instructional and methodical materials, reports the main tendencies and state of organizational work concerning that issue at the district, regional and all-Ukrainian levelsare reflected. The author describes the organizational forms of studying, generalization and implementation of the advanced teaching experience as well as during the training preparation at the Teachers’Training Institutes, and inter-course period (schools of advanced teaching experience, teacherʼs days, catalogue of advanced teaching experience, etc.).